The mae1 gene of Schizosaccharomyces pombe encodes a permease for malate and other C4 dicarboxylic acids - Grobler, Jandre (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc) -- Stellenbosch University, 1995.